ARTIFICIAL INTELLIGENCE–BASED MANAGEMENT OF PATIENT FLOW AND REDUCTION OF INFECTIOUS DISEASE RISKS - Isroilov Ulugbek Begali ogli; Mamadaliyeva Mohlaroyim (Modern American Journals, 2026)
This article highlights the significance of Artificial Intelligence (AI) technologies in managing patient flow and mitigating the risk of infectious diseases within healthcare institutions. AI algorithms enhance the quality of medical services by predicting patient arrival flow, optimizing queues, automating real-time triage processes, and balancing departmental workloads. Furthermore, the article examines the possibilities of using AI for early detection of infectious diseases, isolating high-risk patients, contact tracing, modeling the probability of infection spread, and automating disinfection processes. The advantages of AI, its technical foundations, and the limitations encountered during its implementation are analyzed. Research findings indicate that the effective application of artificial intelligence in medical facilities serves to regulate patient flow and significantly reduce the transmission of infections.
Keywords: Artificial Intelligence (AI), Patient Flow Management, Infectious Diseases, Virtual Queuing, Triage System, COVID-19, Queue Optimization, Infection Control and Safety.